FORMULATION, OPTIMIZATION AND EVALUATION OF QUICK DISPERSIBLE TABLETS OF SUMATRIPTAN - Baghel, Pragya; Roy, Amit; Chandrakar, Shashikant; Bahadur, Sanjib; Bhairam, Monika (Creative Pharma Assent, 2019)
The main objective of this study was to prepare Quick Dispersible Tablets of drug Sumatriptan Succinate, which can rapidly disintegrate in the saliva using three different Superdisintegrants that is, Sodium Starch Glycolate, Crospovidone, and Croscarmallose Sodium with Taste Masking Polymer Beta-Cyclodextrin and Aspartame as a Sweetener. The taste masking of the drug was done by mixing it with the polymer beta-cyclodextrin using Solvent Evaporation method and then mixing optimized quantity of aspartame to it. The Quick Dispersible tablets were prepared by Direct Compression Technique using taste masked drug and other formulation excipients. The effect of various Superdisintegrants in three different concentrations has been studied. The prepared tablets were evaluated for wetting time, In-vitro Disintegration time, strength, and in-vitro Dissolution time. As per the results obtained, it was found that the formulation batch no. 4 was found to be the best formulation, as the data?s obtained by it was found to be in the required range of mouth dissolving tablets.